Comparative study of modified greenhouse solar dryer with north wall materials. (2021) - Purusothaman, M.; Valarmathi, T.N.
Highlights: The performance of the proposed dryers is evaluated with grapes. The moisture content of grapes was reduced from 60% (w.b) to 32% (w.b). Parabolic dryer with insulation took 5 solar days to dry the grapes. Parabolic dryer with insulation results superior quality than other dryers. Abstract: The solar energy is very plenty which is used to remove the moisture level in the food material and to preserve the food material. The aim of this experiment is to evaluate the performance of greenhouse solar dryer using North Wall insulation. When the food products are placed inside the dryer, due to the high temperature inside the dryer when compared to the atmospheric temperature will lose the moisture content in them quickly and gets dried within a short span of time. The dryer is covered with PVC sheet and the construction of the dryer is made up of Wood. The dimensions of the dryer are 1 m length and 0.75 m height are constructed. Inside the dryer stainless steel tray is placed in which the food materials are kept for drying. Below the tray a black sheet is kept at certain distance for absorbing the maximum heat from sun which helps to increase the temperature inside the dryer. Through drying in solar dryers the food material temperature can be observed till 61 °C as a result the moisture inside the food material can be dried more quickly, also there will be a steady decrease in the moisture inside the solar dryer from 60% to 32%. By these observations and results the food material placed in the parabolic dryer with insulation has given the best drying performance which took 5 days to complete the drying process followed by the triangular dryer with insulation took 5 and half days to complete the drying process. The parabolic dryer without insulation took 6 days and triangular dryer without insulation took 6 and half days to complete the drying process and the open drying process has taken 8 days to complete the entire drying process.